Mepyramine maleate treatment of urticaria in horses; a multi-centered, randomized, placebo controlled, double blinded clinical trial - Ural, Kerem; Ulutas, Bülent (Revista Científica de la Facultad de Ciencias Veterinarias)
The aim of the present study was to investigate the efficacy of mepyramine maleate in horses with urticaria. A total of 31 horses, between the ages of 1 and 8 years, were enrolled and randomly assigned to either a placebo or an intramuscular mepyramine maleate group. Clinical evaluations were done by the same investigator, who scored clinical healing, throughout the study and was blinded to the allocation to the groups. At the end of the trial, mepyramine maleate treatment significantly decreased (P<0.001) the investigator”™s clinical scores and while weak changes were detected in the placebo treatment group. In all of the horses treated, the lesions improved gradually within 6 hours after treatment. Complete clinical remission was detected within 6 to 18 hours and all treated horses completely cured within 24 hours of starting treatment. Urticaria was still evident in 8 out of 14 untreated control horses throughout the study. No recurrency was observed in treated horses within 1 week after therapy. Results of the present study indicate that mepyramine maleate may be a safe and effective therapy for horses with urticaria.